A proposal for teaching Object-Oriented Programming to undergraduate students. (8th June 2009) - Xinogalos, Stelios
Various teaching approaches have been proposed for teaching Object-Oriented Programming (OOP) to novices. In this paper we present the results of studying students' conceptual grasp of OOP concepts in two distinct teachings based on the educational programming environments BlueJ and objectKarel. Also, students' replies regarding the effectiveness of objectKarel as a medium of introducing novices to OOP and preparing them for a transition to a conventional OOP language are presented. The main contribution of this paper relates to a new proposal for teaching OOP to undergraduate students, which is based on the combined use of objectKarel and BlueJ.